Lengua e integración social en tiempos del creciente discurso anti-inmigración: Retos para el profesorado y el alumnado migrante adulto en la Unión Europea - Reyes, Charo; Carrasco Pons, Sílvia; Narciso Pedro, Laia (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2021)
This article analyses the structural barriers affecting the processes of linguistic integration among adult migrants and refugees by focusing on both teachers’ and learners’ experiences in the context of an EU-funded project for good practice exchange. Reflections and assumptions of language teachers for migrants and refugees from four European countries (Spain, Germany, Italy and Poland) are set against the linguistic needs and expectations of their students through the case of a Pakistani migrant woman in Barcelona. Although language training for migrants’ labour integration and participation is widely emphasized by supranational, national and regional institutions, it is not a genuine priority in most of the countries of reception. Limited training focused on issues related to language and anti-immigration and/or nationalist discourses condition well-intended initiatives from third sector organisations. Moving away from purely pedagogical factors, this article aims to contribute to locating language learning as social integration under the lens of social justice.